If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.1(43) + 0.35x = 0.05(x + -14) Multiply -0.1 * 43 -4.3 + 0.35x = 0.05(x + -14) Reorder the terms: -4.3 + 0.35x = 0.05(-14 + x) -4.3 + 0.35x = (-14 * 0.05 + x * 0.05) -4.3 + 0.35x = (-0.7 + 0.05x) Solving -4.3 + 0.35x = -0.7 + 0.05x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.05x' to each side of the equation. -4.3 + 0.35x + -0.05x = -0.7 + 0.05x + -0.05x Combine like terms: 0.35x + -0.05x = 0.3x -4.3 + 0.3x = -0.7 + 0.05x + -0.05x Combine like terms: 0.05x + -0.05x = 0.00 -4.3 + 0.3x = -0.7 + 0.00 -4.3 + 0.3x = -0.7 Add '4.3' to each side of the equation. -4.3 + 4.3 + 0.3x = -0.7 + 4.3 Combine like terms: -4.3 + 4.3 = 0.0 0.0 + 0.3x = -0.7 + 4.3 0.3x = -0.7 + 4.3 Combine like terms: -0.7 + 4.3 = 3.6 0.3x = 3.6 Divide each side by '0.3'. x = 12 Simplifying x = 12
| 1-2x=1+6x | | y=6x(x-1) | | -430+.35x=.05x-280 | | 10a-5c+12a-8c= | | 5x-2=-1+4x | | 18d+r=100 | | 3y-7=y+1 | | .15y+.08(y+9000)=2100 | | 3n-1=-1-4n | | 1.29x=21+0.99 | | 80.115= | | 4a-3a=19 | | -10+5k=1k-6+2k | | 8x+1=x | | 2x-7=2x-9 | | 3-1r=-7-6r | | 3-6r=-7+4r | | 5n-2=3+6n | | 8x+3=11x-15 | | 5+2p=3+4p-1p | | 3n*7=-36 | | 1x-6=-3x+6 | | 4x-8=4+8 | | 39-3x=9-9x | | 3n+7=-36 | | -2+2a=-5+3a | | 4x+40=11 | | 3v-3+5v=4v+9 | | 1v-6=6+1v-6v | | 1=5/9(f-32) | | 6p-q^2= | | 1=5/9(f-3) |